ANALISA JUMLAH PRODUKSI GARAM YANG MENGGUNAKAN TEKNOLOGI GEOISOLATOR DI KABUPATEN BIMA SELAMA TAHUN 2016 - 2021 - Nurul Fatimah Yunita; Dewi Merdekawati; Beryaldi Agam (Universitas Djuanda, 2022)
Bima district is a biggest salt producer in West Nusa Tenggara Province. In the salt process production in this region, one of the method used is geoisolator technology. So that the purpose of this research is to analyze the amount of salt production that used geoisolator technology. The data were used are the data for 2016 – 2021. The result show that the centered of salt production using geoisolator technology located in sub district Bolo, Lambu, Woha and Palibelo. The highest production is in Sanolo sub district with the amount of production is 62526,37 Ton and the lowest production is in Pali Belo sub district with the amouth of production is 4698,4 Ton. Furthermore on the overall annual data, show that the production in 2016 is the lowest and the highest production can be seen in 2020 with the amount of 36628,7 Ton.